Evaluasi Strategi Komunikasi Pemasaran pada Program Java Ballon Attraction 2022 oleh Dinas Pariwisata dan Kebudayaan Kabupaten Wonosobo - Wicakso, Anggit Dwi; Urfan, Noveri Faikar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Java Ballon Attraction is an activity created as a collaboration between the Wonosobo Regency Tourism and Culture Office and the Wonosobo Balloon Community. Java Balloon Attraction is an activity that displays sizeable hot air balloon attractions with various motifs being tethered. This is done so as not to disrupt flight traffic. The balloon attraction forms various tourist formations in Wonosobo Regency, such as the shape of Mount Sindoro, Telaga Menjer, and other tourist attractions. The Wonosobo Regency Tourism and Culture Office organized this annual activity, which started in 2019. This research evaluates the marketing strategy implemented by the Wonosobo Regency Tourism and Culture Office in the 2022 Java Balloon Attraction activity. This study used a descriptive qualitative method. Data collection uses observation, interview, and documentation techniques. The data analysis process in this research uses the short-term evaluation theory proposed by Tom Watson and Paul Noble. This research shows several findings, including that at the planning level, some misperceptions make the division of work less clear. At the implementation stage, the marketing publications were not carried out according to schedule, the implementation of promotional media needed to be carried out according to planning, and it was necessary to evaluate the measurement of response targets on social media. The marketing strategy implemented by the Wonosobo Regency Tourism and Culture Office for the 2022 Java Ballon Attraction activity did not work optimally.